Sn-Zn-Bi-Ga system alloys for lead-free soldering, obtained by rapid solidification - Gusakova, Olga V.; Shepelevich, Vasiliy G. (Journal of the Belarusian State University. Ecology, 2021)
The paper presents the results of studying the structural-phase state of the foil of Sn-Zn-Bi alloys of eutectic and near-eutectic compositions doped with Ga, obtained by rapid quenching from the melt at a melt cooling rate of 105 K/s. Using the techniques of X-ray diffraction analysis, scanning electron microscopy and X-ray spectral analysis, it has been established that the foil solidifies with the formation of a tin-based solid solution supersaturated with zinc, bismuth and gallium; its microstructure is formed as a result of the decomposition of the solid solution at room temperature and the formation of zinc inclusions. The homogeneity of the composition and distribution of bismuth and gallium and zinc inclusions over the volume of the foil was established. It was shown by the method of diffraction of back reflected electrons that the foils have a microcrystalline structure. The processes of coarsening of the microstructure during aging at room temperature have been studied.The features of the influence of the gallium concentration on the microstructure, the grain structure and stability of rapidly solidified foils are revealed.
Keywords: tin; zinc; gallium; bismuth; rapid solidification; microstructure; grain structure